Do All Hospital Systems Have Market Power? Association Between Hospital System Types and Cardiac Surgery Prices. (11th November 2019) - Choi, Sung W.; Dor, Avi
Objective: This study explores the price implications of hospital systems by analyzing the association of system characteristics with selected cardiac surgery pricing. Data Source: Using a large private insurance claim database, the authors identified 11 282 coronary artery bypass graft (CABG) cases and 49 866 percutaneous coronary intervention (PCI) cases from 2002 to 2007. Study Design: We conducted a retrospective observational study using generalized linear models. Principal Findings: We found that the CABG and PCI prices in centralized health and physician insurance systems were significantly lower than the prices in stand-alone hospitals by 4.4% and 6.4%, respectively. In addition, the CABG and PCI prices in independent health systems were significantly lower than in stand-alone hospitals, by 15.4% and 14.5%, respectively. Conclusion: The current antitrust guidelines tend to focus on the market share of merging parties and pay less attention to the characteristics of merging parties. The results of this study suggest that antitrust analysis could be more effective by considering characteristics of hospital systems.